Coleção Carmen Sousa do Museu da Universidade Federal do Pará - MUFPA: uma análise do acervo pelo processo de documentação museológica - ROSA, Sandra Regina Coelho da (2019)
The present research aimed to analyze and propose the systematization of Museum documentation to the collection of artist Carmen Sousa (1908-1950), preserved by the Museum of the Federal University of Pará - MUFPA. The collection is composed of collections of Visual Art (painting, sculpture and drawing) and Communication (letters, diaries, photographs, newspaper clipping and others). The justification of the study was intended to broaden the understanding of the research collection, linking the artistic works and documents, in order to promote the recovery of information in relation to the trajectory of the life and work of this artist. As a methodological instrument applied was accomplished through investigative and exploratory studies of objects and documents, packed in technical reserve of the Museum, by aligning them with the theoretical-practical filter the actions and procedures of documentation for Museum Collections. The results achieved by this work aimed at creating a proposal.